2008
DOI: 10.1099/vir.0.2008/003970-0
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus-encoded LMP1 induces a hyperproliferative and inflammatory gene expression programme in cultured keratinocytes

Abstract: SCC12F cells are a line of keratinocytes that retain the capacity for terminal differentiation in vitro. We showed previously that the Epstein-Barr virus (EBV)-encoded oncogene latent membrane protein 1 (LMP1) altered SCC12F morphology in vitro, downregulated cell-cell-adhesion molecule expression and promoted cell motility. In organotypic raft culture, LMP1-expressing cells failed to stratify and formed poorly organized structures which displayed impaired terminal differentiation. To understand better the mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 73 publications
3
24
1
Order By: Relevance
“…Identification of the gene(s) responsible for these effects would be of considerable interest. Surprisingly, the abundance of most cell RNAs did not change substantially after 9 h. These results contrast with a prior study, in which LMP1 induction of IL-1␣ and IL-1␤ was suggested to secondarily account for most LMP1 effects on epithelial cell RNA regulation (45). Indeed, LMP1 TES2-inducible expression activates NF-B more robustly than culture of the cells with high concentrations of IL-1␤ (unpublished data).…”
contrasting
confidence: 56%
“…Identification of the gene(s) responsible for these effects would be of considerable interest. Surprisingly, the abundance of most cell RNAs did not change substantially after 9 h. These results contrast with a prior study, in which LMP1 induction of IL-1␣ and IL-1␤ was suggested to secondarily account for most LMP1 effects on epithelial cell RNA regulation (45). Indeed, LMP1 TES2-inducible expression activates NF-B more robustly than culture of the cells with high concentrations of IL-1␤ (unpublished data).…”
contrasting
confidence: 56%
“…Cellular phenotypic changes observed in this study are consistent with those previously described as accompanying increased levels of LMP1 expression (18,32,36,43). In shortterm proliferation assays, the 8TR CCL20.2/B95-8 clone expressing intermediate levels of LMP1 grew fastest, whereas the 12TR clone with the least and 6TR clone with the greatest LMP1 grew slower, if at all.…”
Section: Discussionsupporting
confidence: 79%
“…Growth and morphological alterations in TR-defined clonal populations. Forced expression of LMP1 in transfection assays has been reported to produce striking alterations in epithelial cell morphology, characterized by a loss of the original cuboidal appearance and the development of a more fusiform morphology (18,32,36,43). Surprisingly, when expressed here in the physiologically relevant context of virus infection, LMP1 conferred on the three clones of the CCL20.2 carcinoma cell line a graduated change in phenotype that paralleled stepwise increases in LMP1 expression levels (Fig.…”
Section: Lmp1 Expression Varies Inversely To Tr Numbermentioning
confidence: 98%
“…EBV LMP1 is a potential candidate because its expression is upregulated during lytic infection and it can induce COX-2 and PGE 2 in NPC cells (9,48). A recent study using microarray analysis shows that LMP1 also augments transcription of GM-CSF in keratinocytes (46). In addition, multiple roles of LMP1 in immune evasion have been reported (45).…”
Section: Discussionmentioning
confidence: 99%